Investigating the impact of emotional intelligence on job satisfaction, and work self-efficacy among nurses in Hail Region, Saudi Arabia - Maha Sanat Alreshidi (Hail Journal of Health Sciences, 2022)
Introduction: The causality of the linkages among emotional intelligence, job satisfaction, and work self-efficacy must be clearly articulated to provide managers with a better understanding of organizational dynamics. This study aimed to determine the relationships among emotional intelligence, job satisfaction, and work self-efficacy. Methods: This research employed a descriptive cross-sectional study design. It was conducted in the northern region of Hail, Saudi Arabia. The study participants were staff nurses who were employed in government-subsidized hospitals. There were 209 participants, and they had a 95.9% response rate. Results: The job satisfaction of the participants was ambivalent (3.47 ± 0.175), with moderate work self-efficacy (3.70 ± 0.504), and high emotional intelligence (4.73 ± 0.156). The direct effect of self-efficacy on emotional intelligence was positive, but not significant (β =0.0107, P = 0.6209), and the direct effect of emotional intelligence on job satisfaction was negative and not significant (β = −0.1484, P = 0.0561), and the direct effect of self-efficacy on job satisfaction was not significant (β = −0.0116, P = 0.6276). Conclusion: The job satisfaction of the participants was ambivalent with moderate work self-efficacy and high emotional intelligence. There was no direct link found among emotional intelligence, work self-efficacy, and emotional intelligence. This suggests that managers and administrators need to pay close attention to the specific circumstances that lead to employees' self-efficacy, emotional intelligence, and job satisfaction showing up in more significant organizational commitment and performance.